The Need for Information Technology to Support Bela Negara on UPN “Veteran” of East Java - M. Syahrul Munir; Fetty Tri Anggraeny (Nusantara Science and Technology Proceedings)
Universitas Pembangunan Nasional Veteran of East Java has a mission to become an ”Unggul berkarakter Bela Negara” university. Bela Negara is a determination, attitudes and behavior of citizens which are done regularly, thoroughly and integrated. It was inspired by the love of the nation of Republic of Indonesia based on Pancasila and UUD 1945 in ensuring the life of nation and state. As a campus that is committed to apply the concept of Bela Negara characters, UPN “Veteran” of East Java is always working so that the academic community (Employees and Students) can understand and interpret the concept of Bela Negara. In this research we propose to apply Bela Negara in a mobile application using waterfall method. To perform needs analysis, data/information is collected through questionnaires. Questionnaires uses 5 variations of values Strongly Agree (SA), Agree (A), Less Agree (LA), Disagree (D), and Strongly Disagree (SD). Based on result of requirement analysis using questionnaire instrument from 51 respondents obtained 29,41% SA, 58,82% A, 11,76% LA, 0% D, and 0% SD stated that Bela Negara can be applied to information technology.